From the community to the emergency department: A study of hospital emergency department nursing practices from the perspective of carers of a loved one with Borderline Personality Disorder. (1st September 2021) - Acres, Kristy; Loughhead, Mark; Procter, Nicholas
Abstract: Carers of loved ones with Borderline Personality Disorder (BPD) often present to Emergency Departments (ED) during acute crisis situations. The initial contact for the carer and consumer in distress is often an emergency nurse. By gaining a greater understanding of carers (18+) perspectives on ED nursing practices when consumers with BPD are requiring crisis support, knowledge about preferred and best practice can be gained. To obtain this knowledge, four semi‐structured focus group interviews were undertaken with a purposive sample of 13 carers through existing carer networks. Transcripts were analysed thematically to identify shared experiences and perspectives across interviews. Four key themes emerged: challenges in accessing crisis support, the need for communication, stigmatising practices, and different levels of care. Findings highlight the ED is viewed as a frontline service which has the capacity to link with another specialist supports when in crisis. Despite this; Communication, confidentiality issues and stigmatising practices continue. The results of this study have implications for nursing practice in the ED, providing important insights that can potentially benefit the carer, consumer and the ED to improve the quality of care offered for people in crisis.